The Strategic Role of Muslims in Realizing Social Harmony in Papua - Darus, Muhammad Rifai; Jubba, Hasse; Abdullah, Irwan; Qodir, Zuly (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2025)
Papua faces complex socio-religious dynamics with the potential for conflict among religious communities. This article explores the strategic role of Muslims in building social harmony. The data used as the basis for analyzing this article was obtained through observation, interviews, and literature studies. The results show that the Muslim community plays an active role as a “creative minority” by integrating moderate Islamic values and the socio-cultural context in Papua. Involvement in the Forum Kerukunan Umat Beragama (FKUB), social programs, and collaboration with religious leaders, local communities, and the government are key in strengthening tolerance and openness. This study contributes to the integration of the concepts of social capital and Islamic moderation in social-religious studies that emphasize the importance of the involvement of religious communities in realizing harmonious social life in a multicultural society. From this it can be seen that to realize and maintain harmony in Papua requires a multidimensional approach involving continuous dialogue, policy support, and the use of local wisdom. Therefore, further research is recommended to explore the perspectives of other religious communities in presenting inclusive dialogue to realize and maintain a harmonious social life among religious communities.